KEMAMPUAN LITERASI MATEMATIS DAN EFIKASI DIRI SISWA MADRASAH TSANAWIYAH - Ranti, Mayang Gadih (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2023)
The purpose of this study was to describe the mathematical literacy skills and self-efficacy of Madrasah Tsanawiyah students and examine the relationship between the two. The research method used is quantitative descriptive and is a correlational study. The research was conducted on 105 class VII students of MTsN 6 Banjar by using a mathematical literacy ability test and a self-efficacy questionnaire. The results showed that students' mathematical literacy skills had an average value of 61.03 and were in the good category, while self-efficacy had an average value of 61.21 and were in the high category, and through the product moment correlation test it was found that there was a positive relationship between students' ability mathematical literacy and student self-efficacy